Clinical features and outcomes in kidney transplant recipients with COVID-19 pneumonia: a single center retrospective cohort study - Xu, Liang; Chen, Xiuxiu; Yang, Xuying; Chen, Song; Yang, Meng; Yuan, Zehua; Chen, Rentian; Wang, Jianli; Jiang, Hongtao; Xu, Jian (Frontiers in Cellular and Infection Microbiology, 2024)
ObjectiveThis retrospective cohort study aimed to assess the clinical features, treatment outcomes, and short-term prognosis in kidney transplant recipients (KTRs) with concurrent coronavirus disease 2019 (COVID-19) pneumonia.MethodsKTRs with COVID-19 pneumonia who were admitted to our hospital from December 28, 2022, to March 28, 2023 were included in the study. Their clinical symptoms, responses to antiviral medications, and short-term prognosis were analyzed.ResultsA total of 64 KTRs with initial diagnosis of COVID-19 pneumonia were included in this study. The primary symptoms were fever, cough, and myalgia, with an incidence of 79.7%, 89.1%, and 46.9%, respectively. The administration of antiviral drugs (paxlovid or molnupiravir) within 1–5 days and for over 5 days demonstrated a statistically significant reduction in viral shedding time compared to the group without antiviral medication (P=0.002). Both the paxlovid and molnupiravir treatment groups exhibited a significantly shorter duration of viral shedding time in comparison to the group without antiviral drugs (P=0.002). After 6 months of recovery, there was no significantly negative impact on transplant kidney function (P=0.294).ConclusionFever, cough, and myalgia remain common initial symptoms of concurrent COVID-19 pneumonia in KTRs. Early use of antiviral drugs (paxlovid or molnupiravir) is associated with better therapeutic outcomes. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) had a limited impact on the short-term renal function of the KTRs with concurrent moderate or severe COVID-19 pneumonia.